Late Coetzee Revisited - Chesney, Duncan McColl (International Journal of English Studies, 2022)
In this paper I reassess the discussion of Coetzee and late style by focusing on the criticism from around the time of Elizabeth Costello in order to observe if these treatments, and the concept of lateness developed by Adorno and Said, help us to understand the late, late Jesus trilogy. After reviewing the crisis in the novel exemplified by the Dairy I turn to an analysis of the Jesus novels and then finally assess the discussion of Coetzee in recent work in World Literature. The late, late works of Coetzee do not fit exactly within the existing critical discussion of late Coetzee; yet, they cannot be easily subsumed within an account of the post-historicist, global novel. These novels, while not Coetzee’s best, must still be understood within the history of Coetzee’s own development as a writer. Precisely, this attention to continuity helps reveal both strengths and weaknesses of late, late Coetzee.